BELIEFS ABOUT CONSTRUCTIVIST-ORIENTED TEACHING PRACTICES: A STUDY WITH ELEMENTARY PHYSICAL EDUCATION TEACHERS - Luciano Gonzaga Galvão; Ana Flávia Backes; Rodolfo Silva da Rosa; Vinicius Zeilmann Brasil; Leonardo Ristow; Jéssica Dias Cardoso; Juarez Vieira do Nascimento; Valmor Ramos (Journal of Physical Education)
ABSTRACT The aim was to identify the beliefs about teaching practices oriented to constructivism by Elementary Physical Education teachers of the Florianópolis Metropolitan Nucleus in Santa Catarina, Brazil. In this quantitative and descriptive study, 129 Elementary School Physical Education teachers answered a questionnaire to characterize the participants and a translated and adapted version of the Constructivist Teaching Practices Inventory in Elementary Physical Education - CTPI-EPE. Descriptive statistic and binary logistic regression analysis were used, with the aid of the open-source software “R”, version 3.6.1. The results revealed that regardless of personal, academic, and professional characteristics, the Physical Education teachers investigated perceive their teaching often oriented towards constructivism. It stands out, teachers with a temporary job often have beliefs related to teaching practices oriented towards general constructivism; teachers who did not participate in courses on sports education have beliefs oriented to the development of social cooperation; and teachers with a temporary employment bond and with a non-degree graduate program had a greater chance of promoting students' personal relevance in their classes.